PEMAKZULAN PRESIDEN DALAM PERSEPSI KONSTITUSI (STUDI KASUS PRESIDEN ABDURRAHMAN WAHID) - arie sulistyoko (Syariah: Jurnal Hukum dan Pemikiran, 2016)
The affirmation of state idea that based upon the law proves that the law is put in an important position in the life of the state as the embodiment of the sovereignty of law. Therefore, every attitude, policy, action or behavior of tools and citizens in the life of the nation obey the applicable rules or laws. It is applied equally to every citizens, no exception to the President as head of state and government. Before the changes to the 1945 Constitution, the President and/or Vice-President can be dismissed for reasons that are political, not judicial. It is happened to President Abdurrahman Wahid that was dismissed from office by the Assembly by not using the constitution of the Republic of Indonesia of 1945 as the legal basis but using TAP MPR number III year 1978.